Organizational Information Processing, Competitive Responses, and Performance in the U.S. Domestic Airline Industry - Smith, Ken G.; Grimm, Curtis M.; Gannon, Martin J.; Chen, Ming‐Jer (Academy of Management Journal, 1991)
This study investigates how firms build competitive advantage by focusing on the actions and responses of rivals in the U.S. domestic airline industry. We identified four attributes of competitive response- imitation, likelihood, lag, and order-explaining them in terms of the information represented in the type of action to which a firm is responding and the information-processing characteristics and capabilities of the responding firm. We tested the importance of response as it relates to competitive advantage by linking response with performance. Findings supported the notion that a firm?s response can be predicted from the manner in which it interprets and processes information. Further, three of the four response characteristics were related to performance.